ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA GIANYAR - Putu Wenny Saitri (Universitas Triatma Mulya, 2022)
Tax is a taxpayer contribution to the state owed by every person and entity that is coercive. To achieve this, the role of citizens is very important in contributing to paying taxes to increase state revenue. This research aims to test and obtain empirical evidence of the influence of taxpayer awareness, trust in government, tax knowledge, application of e-filing and tax sanctions on the compliance of individual taxpayers in KPP Pratama Gianyar. The population of this study is all taxpayers registered with KPP Pratama Gianyar. The sample in the study was as many as 100 private taxpayers determined based on accidental sampling methods. The analytical tool used to test hypotheses is multiple linear regression analysis. The results showed that the variable application of e-filing had a positive effect on taxpayer compliance. While taxpayer awareness, trust in government, tax knowledge and tax sanctions have no effect on taxpayer compliance in KPP Pratama Gianyar. Further research is expected to develop this research by increasing the number of samples and using other variables that have an influence on taxpayer compliance such as the use of e-billing systems.